The History of Prostitution in Yogyakarta during the Colonial Era - Alliyah Nur Khofifah (Jurnal Perempuan dan Anak, 2023)
Prostitution is an illegal activity that has existed since the colonial era. The history of prostitution, especially in Yogyakarta, has existed for a long time. Yogyakarta, which is a tourism city, also has illegal destinations, such as prostitution. The history of prostitution began when there was a railroad construction project, prostitution activities also began to experience growth. But even so, the government did not just remain silent, that's why several policies were issued regarding this prostitution. Because at that time the existence of prostitution had quite a significant impact on the social, economic and health sectors. Departing from this, this study on prostitution aims to provide an overview of how prostitution began in Yogyakarta, and how the government has acted in dealing with this prostitution problem. This study uses historical research methods which use sources in the form of documents and literature studies that are in accordance with the subject matter of this study. There are several steps used, including heuristics, verification, interpretation, and historiography. The results of this study indicate that prostitution is a means of satisfying the sexual appetite of railroad project workers. In addition, because it experienced significant developments, in the end several policies were issued regarding this prostitution. because the existence of this prostitution has an impact on society, especially service providers and perpetrators of prostitution. Apart from that, it also has health impacts, such as the emergence of venereal diseases or what is known as syphilis.